Factors That Influence Consumers’ Purchase Intention towards Ambient Advertising in Malaysia - Shen, Jiayuan (2014)
As the economic growth, the per capita national income has increased (The World Bank, 2013). In order to adapt to the need of high standard of living in Malaysia, thus, more and more business brands have appeared in Malaysia’s market cater, and more substitutes and advertising also become more and more. However, the attraction for the customers is an important task for any company that makes great efforts to its advertising for the products. As is known to all, the value and the cost for traditional Medias are lack of attract for business for their higher investment and low return. Furthermore, too many of the advertising information contains true and false news runs around the people live, which cause changes for the trust level of advertisements. However, traditional Media were found to have marketing for business. Ambient advertising is created as new way to attract the customers, and it has taken advantages of use these attractions for business development in Malaysia. The marketers have used these ambient advertising to promote their products and strengthen their existing brands. The company hopes to sell products through the changes and surprises of ambient advertising, and the company also wants to motivate purchasing intention. This thesis made the researchers for the factors affecting the customers’ attitudes for the ambient advertising in Malaysia. The author interest in collecting a number of data to support the views, and 300 questionnaires were assigned to three cities in Malaysia. The methodology in this thesis used positive analysis and SPSS20.0 (PLS) to get efficient and valid analysis and studies. The results showed that ambient advertising was a kind of emerging advertisements form as a special channel to send product information to the passenger relative to traditional ways, which was a more direct and more interesting way to make customers feel the surprised and curious. At the same time, the ambient advertising is an indirect way to transfer the brand information such as the brand’s mission, vision and knowledge, to the customer, in addition, the efforts of ambient advertising are more obvious, and the cost of ambient advertising is low comparison with the traditional media. However, the using rate for ambient is not very satisfied. So, this research concentrates on factors affecting consumers’ purchase intention towards ambient advertising in Malaysia’s three cities to make an explored study because the using rate of ambient advertising is lack. The results of factors analysis have scientific and objective significance for later researchers.